Asma e obesidade: determinação de um perfil inflamatório e funcional em mulheres obesas asmáticas - Rosa, Gilvandro De Almeida [UNIFESP] (2019)
Introduction: Asthma and obesity are two chronic diseases, difficult to manage and of high and increasing prevalence in several countries of all continents; in Brazil the two diseases are a serious health problem, causing high costs for public health. About two decades ago, some studies have shown a higher prevalence of asthma among obese, especially among obese women. Some affirm that the fact is due to the particular physical-structural alterations of the obese ones, leading to the collapse of the bronchi, leading to the bronchial hyper-reactivity. Others, however, suggest that adipose tissue has been described in the last twenty years as an endocrine tissue, demonstrating the production of lipidectin (adipokine and adipoctin), as well as other inflammatory mediators, including various types of interleukins and Tumor Necrosis Factor (TNF). This excess of inflammatory mediators, in the obese, would play an important role in the chronic inflammatory process in the obese, in which one of the target organs would be the lung. Method: Our work studied 73 obese women (51 asthmatic obese and 22 non-asthmatic obese women), who underwent clinical interviews - Application of the ACQ questionnaires from the Global Initiative for Asthma (GINA) and the International Study for Asthma and Athopy in Chilhoold (ISAAC), spirometry, methacholine bronchial provocation test, blood collection for laboratory tests, and for dosage of inflammatory mediators, aeroallergens (prick-test) skin test, nasal swab cytology and induced sputum. Objective: to determine the functional and inflammatory profile of asthma in obesity. Results: Groups were demographically similar (age, BMI and past smoking). However, completely different in the cytology of nasal swab and induced sputum, prick test, total serum IgE, spirometric values and bronchial provocation test with methacholine. At the dosages of leptin that was four times higher in the asthmatic obese group. Conclusion: We conclude that obese asthmatic follows the Th2 inflammatory pattern with high IgE; however, hyperlipectinemia may interfere with the inflammatory process. The phenotype of bronchial asthma in obese individuals would be represented predominantly by a Th2 response, with production of high levels of serum leptin, which may exacerbate or induce this inflammatory response.